2018
DOI: 10.3762/bjnano.9.9
|View full text |Cite
|
Sign up to set email alerts
|

Growth model and structure evolution of Ag layers deposited on Ge films

Abstract: We investigated the crystallinity and optical parameters of silver layers of 10–35 nm thickness as a function 2–10 nm thick Ge wetting films deposited on SiO2 substrates. X-ray reflectometry (XRR) and X-ray diffraction (XRD) measurements proved that segregation of germanium into the surface of the silver film is a result of the gradient growth of silver crystals. The free energy of Ge atoms is reduced by their migration from boundaries of larger grains at the Ag/SiO2 interface to boundaries of smaller grains n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 33 publications
(46 reference statements)
2
21
0
Order By: Relevance
“…Figure 1a presents survey XPS spectra collected from the very surface of sandwich samples, where a 2-nm-thick layer of germanium is deposited between 20-nm-thick layers of silver and gold. The XPS spectra were collected 30 days after the fabrication of the samples, to allow germanium to fully segregate towards the surface [37]. For comparison, the spectra for sandwich-like structures where the germanium is deposited between two layers of the same metal, measured 10 days after sample fabrication, from works [38,39], are also presented.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Figure 1a presents survey XPS spectra collected from the very surface of sandwich samples, where a 2-nm-thick layer of germanium is deposited between 20-nm-thick layers of silver and gold. The XPS spectra were collected 30 days after the fabrication of the samples, to allow germanium to fully segregate towards the surface [37]. For comparison, the spectra for sandwich-like structures where the germanium is deposited between two layers of the same metal, measured 10 days after sample fabrication, from works [38,39], are also presented.…”
Section: Methodsmentioning
confidence: 99%
“…It has previously been demonstrated that Ge atoms segregate to the surface of Ag and Au layers deposited on germanium wetting films, even in case of metal/Ge/metal sandwich structures [37,38,40]. Such behavior is attributed to non-uniform metal grain size distribution within the depth of the film, as evidenced by X-Ray Reflectometry measurements [37,40].…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations